Relação entre achados ultra-sonográficos e dopplervelocimétricos e dosagens de β-hCG de pacientes em seguimento de doença trofoblástica gestacional: Pacientes admitidas no Ambulatório de Mola da Fundação Santa Casa de Misericórdia do Pará no período de janeiro de 2003 a dezembro de 2004 - SANTOS, Adriana Rodrigues dos (2022)
The Trophoblastic Gestational Disease (DTG) is a set of illnesses that are characterized by the abnormal proliferation of trophoblasts related to pregnancy. Due to few existing literature about the segment of DTG, the authors objectified to correlate, after curettage procedure, the ultrasonographic and dopplervelocimetric findings with the levels of β-hCG in patients with DTG. A retrospective study was carried out, making up a total of 96 patients with Trophoblastic Gestational Disease diagnosis, coming from the Foundation Santa Casa de Misericordia do Pará clinic, in the period of January of 2003 through December of 2004. The information was obtained by protocol-profiles. The majority of the patients (79,2%) presented spontaneous denying of β-hCG and normal ultrasonographic examinations after uterine emptying. In the correlation study between USG findings and the observed values on the β-hCG curve, three groups of patients were defined: 90,6% both compatible examinations to malignity suggestion and for denying the illness that grouped the majority of the patients; 6,3% normal β-hCG and suggestive malignant USG; 3,1% β-hCG suggesting persistent DTG without the concurrence of ultrasonographic findings. It was observed that amongst the patients who presented persistence of β-hCG suggestive values and anormal USG, the majority of patients had the β-hCG as a first indication of the disease persistence. It was concluded that β-hCG is more efficient as a first indication of persistence desease and indication for complement treatment.